EVALUASI KINERJA PROSES ROASTING KOPI BERDASARKAN WAKTU FIRST CRACK PADA DRUM ROASTER DAN HOT AIR ROASTER - warandi , rofandi Rori Aditiar; koswara, engkos (Universitas Majalengka, 2025)
Coffee is one of the most valuable agricultural commodities with increasing consumption both in Indonesia and globally. Roasting is a crucial stage in coffee processing that transforms green beans into roasted beans, developing distinctive aroma, flavor, and color through complex chemical reactions such as Maillard reaction, caramelization, and degradation of organic compounds. One of the key parameters in roasting is the first crack, which indicates the degree of bean development and is often used as a reference to control the roasting profile. This study aimed to evaluate the performance of Drum Roaster and Hot Air Roaster based on the time to reach first crack at three roasting levels (light, medium, and dark) using Robusta green beans with moisture content of 11–12.5%. Experimental results showed that the Hot Air Roaster was more time-efficient compared to the Drum Roaster, with an average reduction of 1 minute and 3 seconds in reaching the first crack. Furthermore, organoleptic Responses indicated that coffee roasted with the Hot Air Roaster produced a stronger aroma compared to the Drum Roaster at all roasting levels. These findings suggest that the Hot Air Roaster provides better efficiency and aroma quality, making it a suitable option for coffee roasting, although the choice of roaster should still consider production needs and flavor preferences.